Digital marketing on Gojek consumer loyalty - Putra, I Komang Mahayana; Sanjaya, Ida Bagus; Wirga, I Wayan; Gede, I Gusti Ketut; Sukarta, I Wayan (International research journal of management, IT and social sciences, 2023)
Consumer loyalty is the customer’s willingness always to use the company’s products in the long term, use them exclusively, and recommend the company’s products to friends or colleagues. This study aims to determine the effect of digital marketing on Gojek’s consumer loyalty. The sample in this study was Gojek consumers in Denpasar City. Determination of the sample in this study using a non-probability sampling method. The number of samples taken was 112 people. Collecting data using questionnaires. Data were analyzed using multiple linear regression analysis techniques. The results of this study indicate that digital marketing has a positive and significant effect on consumer loyalty.